Analisis Penggunaan Dana BOS di SMA Muhammadiyah 4 Jakarta terhadap Permendikbud Nomor 63 Tahun 2023 Tentang Petunjuk Teknis Pengelolaan Dana Bantuan Operasional Satuan Pendidikan - Setiawan, Heri; Miharja, Marjan (HUMANIORUM, 2025)
School Operational Assistance (BOS) is a program to improve education and reduce school operational costs. Although there have been efforts to improve transparency and accountability in the management of BOS funds, monitoring and planning adjustments still need to be enhanced to address external challenges and ensure that the funds used are managed efficiently. The purpose of this research is to analyze the methods used in the management, utilization, and accountability reporting of BOS funds at SMA Muhammadiyah 4 Jakarta as regulated in Permendikbudristek Number 63 of 2023. This research was conducted descriptively qualitatively, and data collection was carried out through interviews and documentation. The research results show that SMA Muhammadiyah 4 Jakarta has managed the BOS funds in accordance with the regulations. However, budget planning is hindered by several obstacles, such as changes to the previously allocated budget. Additionally, there is no effective system in place for managing the use of BOS funds for unexpected needs, such as emergency repair costs, health and safety expenses, and the procurement of additional teaching materials